Inovação educacional no ensino de língua portuguesa: fluência tecnológico-pedagógica e recursos educacionais abertos - Schlotfeldt, Veridiana Veleda Pereira (2024)
This research investigates how the development of Technological-Pedagogical Fluency (TPF) in the process of creating Open Educational Resources (OER) can foster educational innovation in Portuguese Language classes at the high school level. The main goal of the study is to explore the potential and challenges of promoting educational innovation through the development of TPF in the creation of OER for high school Portuguese teaching. Specific objectives include: developing the production and integration of OER into teaching practices of high school Portuguese teachers; analyzing the knowledge acquired and refined through TPF development in OER authorship within the Portuguese language teaching-learning context; and examining how the Brazilian National Common Curricular Base (BNCC) for high school encourages educational innovation in Portuguese language teaching and learning. The research is based on the cartographic matrices proposed by Mallmann (2015), namely: the Dialogical-Problematizing Matrix (MDP), the Thematic-Organizing Matrix (MTO), and the Thematic-Analytical Matrix (MTA). Data collection occurred in 2023 through semistructured interviews with teachers, questionnaires with students, and observations of classroom interactions. Data analysis was guided by Bardin’s Content Analysis (2016), using categories like TPF development in OER production and educational innovation. The study also employed Design-Based Research (DBR), allowing for iterative and collaborative development of educational practices. This framework followed four phases proposed by Herrington et al. (2007), which facilitated the creation of teaching materials aligned with BNCC guidelines and encouraged both teacher and student authorship. Two teachers and their classes from the 2nd and 3rd years of high school in public schools in Rio Grande do Sul and Roraima participated in the study. The research found that teacher-student collaboration is essential for innovative teaching practices, although a lack of educational technologies in schools and insufficient ongoing teacher training are significant challenges. Despite these obstacles, the use of OER contributed to a more collaborative teaching environment. The data indicates that developing TPF is critical for teachers to become critical and reflective, and that awareness of copyright issues is important to promote responsible sharing practices. The study highlights that educational innovation in Portuguese language teaching is linked to strengthening teachers' TPF, fostering collaboration among all stakeholders, and producing OER that are suited to various educational contexts and aligned with the BNCC guidelines. Therefore, as teachers develop their TPF in OER production, they are better able to promote educational innovation in high school Portuguese language classes.